Learner engagement with automated feedback, peer feedback and teacher feedback in an online EFL writing context. (July 2020) - Tian, Lili; Zhou, Yu
Abstract: Research on different feedback sources and their impact on second or foreign language writing have proliferated in the past two decades. However, the way learners engage with multiple feedback sources and the driving force behind their feedback uptake decisions over time in online writing contexts still remain under-examined. This naturalistic case study addresses the gap by looking at how five Chinese learners of English engaged with automated, peer and teacher feedback in an online EFL writing course over a 17-week semester. Textual and interview data indicated a dynamic and reciprocal engagement of learners with different sources of feedback, mediated by a range of individual and contextual factors having interactively influenced learners' decision-making in feedback uptake.